No-Fly Lists, National Security and Race: The Experiences of Canadian Muslims. (20th November 2019) - Nagra, Baljit; Maurutto, Paula
Abstract: Despite the increasing use of no-fly lists in countries like the United States, United Kingdom and Canada, their impact has not been explored in academic research. In a bid to fill this gap, we conducted 70 in-depth interviews with Muslim community leaders to explore Canadian Muslims' experience of the no-fly list. We find the Canadian no-fly list targets Muslim communities, restricts mobility, separates individuals from family and friends, diminishes professional and economic opportunities, and stigmatizes those labelled a security risk. Drawing on the preventive security literature and critical race studies of counter-terrorism, this research demonstrates how no-fly lists erode fundamental aspects of justice, and reproduce racial hierarchies.